Electronic device use by individuals with traumatic spinal cord injury. (4th July 2017) - Mayman, Gillian; Perera, Marisa; Meade, Michelle A.; Jennie, Joanna; Maslowski, Eric
Abstract : Objective : To describe use of several electronic devices among individuals with traumatic spinal cord injury (SCI). Study Design : Cross-sectional survey. Setting : Community. Methods : Potential participants consisted of all individuals with traumatic SCI, ages 7 and older, who had received care through a large academic medical center in the Midwest between January 1, 2003, and January 2, 2013. All eligible individuals received the survey as part of a four-stage mailing that asked questions about electronic device use in addition to questions about demographic and injury-related characteristics. Results : Mailings were sent to 820 individuals; of those, 451 completed and returned the survey. Descriptive and nonparametric statistics were performed. Individuals with high-level tetraplegia were less likely to use tablet and handheld electronic devices than individuals at all other SCI levels. Individuals aged 65 years and older were less likely to own or use tablet computers and handheld devices than all other age groups. Conclusion : While electronic devices hold considerable potential as a treatment modality for individuals who have sustained SCI, there is diversity in the particular electronic devices that are used by such individuals due to injury-related characteristics and age.